The iron-binding proteins of iron-absorbing rat intestinal mucosa - Johnson, Glynis (Division of Clinical Haematology, 2018)
Iron deficiency anaemia is perhaps the most widespread nutritional deficiency disease; as result, the topic of iron absorption has received intensive investigation over a relatively long period of time. Most of the investigative thrust has come from clinical medicine and allied fields, with some associated biochemical investigation. Evidence from the latter has pointed towards the involvement of iron-binding proteins especially ferritin and transferrin in the absorptive process. While the biochemical literature on these two proteins, particularly transferrin, is vast, their roles in iron absorption are obscure. This study was undertaken, therefore, as an investigation into these proteins, their quantitation and role in iron absorption. The physiology of absorption was studied by injection of radiolabelled ferrous ascorbate into isolated intestinal loops and the determination of mucosal, blood and carcass uptake.